2017
DOI: 10.1007/s00414-017-1594-6
|View full text |Cite
|
Sign up to set email alerts
|

An SNP panel for the analysis of paternally inherited alleles in maternal plasma using ion Torrent PGM

Abstract: Researchers have sought to develop an effective protocol for paternity analysis using cell-free DNA (cfDNA) in maternal plasma. The use of massively parallel sequencing (MPS) technology for SNP testing is attractive because of its high-throughput capacity and resolution to single-base precision. In this study, we designed a customized SNP panel for cfDNA sequencing that includes 720 short amplicons (< 140 bp) targeting SNPs on the autosome and Y chromosome. The systemic performance was evaluated using the Ion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…However, it seemed that more markers still needed to be added for the identification of second‐degree or more distant relatives to provide more discriminating power. It should also be noted that though the LR value of individual MH locus was lower than STRs on average, the larger number in the human genome, less artifacts (e.g., stutter peaks) and the shorter length of candidate fragment (restricted within ∼100 bp in the present study) are expected to make this maker more useful in cases of unbalanced mixed sample or degraded DNA, such as the DNA mixture in a crime scene or the cell‐free fetal DNA utilized in the prenatal paternity determination .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, it seemed that more markers still needed to be added for the identification of second‐degree or more distant relatives to provide more discriminating power. It should also be noted that though the LR value of individual MH locus was lower than STRs on average, the larger number in the human genome, less artifacts (e.g., stutter peaks) and the shorter length of candidate fragment (restricted within ∼100 bp in the present study) are expected to make this maker more useful in cases of unbalanced mixed sample or degraded DNA, such as the DNA mixture in a crime scene or the cell‐free fetal DNA utilized in the prenatal paternity determination .…”
Section: Discussionmentioning
confidence: 87%
“…Altogether, 60 MH candidates were primarily screened out from ALFRED database (Allele Frequency Database, Yale University) and previous published literatures (Supporting Information ). Altogether, there were 46 3‐SNPs, 13 4‐SNPs, and 1 5‐SNPs MHs in the candidate panel, spreading across 21 human autosomes.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies based on the Illumina MiSeq platform (Illumina, Inc.) and Ion Torrent PGM platform (Thermo Fisher Scientific) have demonstrated the great potential of the MPS technology in the application of NIPAT. [12][13][14] Meanwhile, several strategies for data interpretation in this field have been also developed. Yang and colleagues 12,14 provided a straightforward nonmaternal allele counting method in maternal plasma for identifying paternal alleles based on a predefined allele fraction cutoff.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Meanwhile, several strategies for data interpretation in this field have been also developed. Yang and colleagues 12,14 provided a straightforward nonmaternal allele counting method in maternal plasma for identifying paternal alleles based on a predefined allele fraction cutoff. Validation of this method in fetal tissues demonstrated that paternal alleles were accurately identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation